2010
DOI: 10.1002/aic.12167
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of liquid CO2 drop formation with and without hydrate formation in static mixers

Abstract: The formation process of CO 2 drops in various types of Kenics Static Mixers was analyzed from the perspective of energy dissipation in the mixer, focusing on the formation of drop surfaces. Experimental studies on CO 2 drop formation were conducted under varying temperatures, pressure, and flow rates, with and without hydrate formation. Analysis of the CO 2 drop size and distribution at several locations within the static mixer was conducted, as of pressure drop in the mixer, to determine dissipation energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…The bubbles have strong turbulent motions and the clusters of small bubbles have a progressive increase induced by the flow division, flow reversal, and radial mixing of static mixing functions. 63 The flow in the gas−liquid system transforms into a heterogeneous flow pattern (Figure 3c,d,g,h) as pointed out by Kazakis et al 60 and Yang et al 61 In addition, these swirl rising bubble clusters are observed in Figure 3d. Obviously, the centrifugal force generated by the swirling structure causes the bubbles to gather toward the center of the element.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The bubbles have strong turbulent motions and the clusters of small bubbles have a progressive increase induced by the flow division, flow reversal, and radial mixing of static mixing functions. 63 The flow in the gas−liquid system transforms into a heterogeneous flow pattern (Figure 3c,d,g,h) as pointed out by Kazakis et al 60 and Yang et al 61 In addition, these swirl rising bubble clusters are observed in Figure 3d. Obviously, the centrifugal force generated by the swirling structure causes the bubbles to gather toward the center of the element.…”
Section: Resultssupporting
confidence: 53%
“…As the superficial gas velocity increases, deformed large bubbles emerge at the middle and ending edge of the element as shown in Figure f–h. The bubbles have strong turbulent motions and the clusters of small bubbles have a progressive increase induced by the flow division, flow reversal, and radial mixing of static mixing functions . The flow in the gas–liquid system transforms into a heterogeneous flow pattern (Figure c,d,g,h) as pointed out by Kazakis et al and Yang et al In addition, these swirl rising bubble clusters are observed in Figure d.…”
Section: Resultsmentioning
confidence: 55%